Gender differences in general knowledge: do residential status and the type of school matter? - Zarevski, Predrag (Array, 2014)
The goal of this study was to examine gender differences in general knowledge related to residential status and type of school. The study included 455 female and 362 male subjects of the third and fourth year of grammar (N=422) and professional affiliations schools (N=395) in the Republic of Croatia. They were from the capital city (Zagreb, N=440) or smaller cities (less than 50.000 inhabitants, N=377). The new 110 item version of the general information test (GIT-2012) was used. GIT-2012 Cronbach alpha for male participants was .89, and for women .85. In accordance with previous studies, the results of this study showed better performance and greater variance of male participants in total score on the GIT compared to female participants. Also, a statistically significant difference in the greater number of general information domains for men was obtained. High school students in Zagreb achieved better results than high school students from other cities, and students in grammar schools were more successful than vocational school students. Hierarchical regression analysis showed that the strongest determinant of general knowledge was type of school, then place of education, and the weakest predictor was gender. This indicates that gender differences in general knowledge in Croatian high students, although statistically significant, are not as important as the type of school and residential status. This result supports gender similarities hypothesis (Hyde, 2005).